The Effectiveness of Chia Seeds ( Salvia Hispanica ) on Increasing Hemoglobin (Hb) Levels to Prevent Anemia (LPPM Universitas PGRI Adi Buana Surabaya, 2025)
Anemia occurs when hemoglobin levels in the blood fall below normal levels. This is a significant health issue, particularly among children, adolescent girls, and pregnant and breastfeeding women. Untreated anemia in adolescents can negatively impact health in adulthood, including the risk of pregnancy complications, which in turn increases the risk of stunting and maternal and infant mortality. Efforts to prevent anemia include consuming foods containing iron, folic acid, and vitamins A, C, and E, supplemented with zinc and supplementation with iron tablets. Chia seeds are a natural ingredient with health potential, the protein and mineral content in chia seeds supports the process of hemoglobin formation to prevent anemia. This research was conducted to evaluate the effects of chia seed consumption on increasing hemoglobin levels. The method used was a quasi-experimental study with pre- and post-tests on two groups. A sample of 80 respondents was selected purposively and divided into two groups. The first group was given 15 grams of chia seeds once daily for 14 days, and the second group received 50 mg of vitamin C twice daily for 14 days. Data were analyzed using a paired t-test. The results showed an increase in hemoglobin levels with an average of 1.3 grams per deciliter and a P value of less than 0.005, which means that giving chia seeds had a effect on increasing hemoglobin levels in female students at the Syamsul Arifin Islamic boarding school. In conclusion, chia seeds are effective in increasing hemoglobin levels to prevent anemia.